Pasteuria thornei, a novel biological seed treatment for root lesion nematode control in soybean and maize - Confort, Pedro Marcus de Souza (2018)
The Pasteuria genus comprises gram-positive bacteria that are obligate parasites of arthropods and nematodes. Species of this genus are ubiquitous, being present in both aquatic and terrestrial environments all around the world. Pasteuria was first described as a genus at the end of the 19th century and has undergone considerable reclassification regarding its member species. Starting in the 1980s, a more meticulous classification effort regarding the identification of Pasteuria spp., and its parasitic habits began. These studies were strongly motivated by the ability of individuals of this genus to parasitize phytopathogenic nematodes of several plant species. Each species of the genus Pasteuria establishes a strict parasitic relationship with a specific genus of phytonematode. As an example of this interaction, Pasteuria thornei is a parasite restricted to the genus Pratylenchus, which comprises the nematodes popularly known as root-lesion-nematodes, a pest of several agronomically important crops. Considering the current relevance of studies involving the biological control of phytonematodes, in the present work three experiments were carried out, each one containing a replicate, totaling, therefore, six experiments. Two experiments were intended to verify the efficacy of P. thornei as a biological control agent (BCA) of Pratylenchus brachyurus in soybean. The remaining four experiments had a similar objective in the scope of the Pratylenchus zeae - maize pathosystem. Two experiments were carried out to verify the efficacy of P. thornei as a biological control agent for P. zeae in maize, and afterwards, two additional experiments were performed in order to verify the capacity of the BCA to reduce productivity losses in corn plants due to the parasitism of this nematode. For the soybean experiments, the following treatments were added to the seeds of the cultivar SYN1080: three different concentrations of P. thornei endospores per seed (5x106, 107 e 1,5x107), a commercial control group for comparison containing abamectin (0.58mg/seed) and a mixed treatment containing abamectin (0.58 mg / seed) and 107 P. thornei endospores. Untreated seeds were used as a control group. The treatments were sown in 500 cm3 plastic cups containing soil inoculated with 1000 nematodes (experiment 1) and 600 nematodes (experiment 2). Fresh root mass and nematodes extracted from the roots of each plant were used as parameters of evaluation, taking place 60 and 90 days after inoculation (DAI). Only the treatment with the highest concentration of P. thornei (1.5x107) reduced the final population of nematodes significantly, reaching 30-50% of reduction compared to the untreated seeds. However, treatments containing the commercial control abamectin were superior in reducing the final population of nematodes in all experiments evaluated. Regarding the maize efficacy experiments, CELERON hybrid seeds were treated as described: four concentrations of P. thornei endospores per seed (5x106, 107, 1,5x107, 2x107), a commercial control group for comparison containing abamectin (0.58 mg / seed) and a mixed treatment containing abamectin (0.58 mg / seed) and 107 P. thornei endospores. Untreated seeds were used as a control group. The treated maize seeds were planted in 500 cm3 plastic cups containing soil inoculated with 4000 and 1000 individuals for the efficacy experiments 1 and 2, respectively. Evaluations occurred at 60 and 90 DAI. For the productivity assays, the experiments 3 and 4 were carried out under a screened greenhouse, with experimental plots consisting of 9L pots filled with artificially infested soil. Seeds of the CELERON hybrid received the following treatments: abamectin (0.58mg / seed), P. thornei (107 endospores / seed) and mixed treatment containing both abamectin (0.58mg / seed) and P. thornei (107 endospores / seed). Two additional treatments containing untreated seeds served as controls, with and without the presence of Pratylenchus zeae. The evaluation measured several agronomic traits, such as dry weight of the aerial parts, fresh mass of roots at harvest and total weight of grains. In addition, the nematode population was measured in fresh roots at 45, 90 days and at the time of harvest. Efficacy trials showed that the highest concentrations of P. thornei (1.5x107 and 2x107) have a considerable potential of P. zeae control. The nematode population reduction was 54 and 47% in experiments 1 and 2, respectively, for the highest P. thornei concentration treatment. The commercial formulation containing abamectin showed a reduction of P. zeae population above 90% in both experiments. Regarding the maize productivity experiments, control potential of nematodes by P. thornei was similar to that observed in the efficacy study. The treatments containing abamectin had an effect on the mitigation of yield losses caused by P. zeae in both experiments. The mixed treatment (abamectin and P. thornei) and the one containing exclusively P. thornei presented a positive performance in both replicates. In none of the experiments synergistic or additive effects were observed between P. thornei and abamectin. With the data obtained in these experiments, the control potential of P. thornei on P. brachyurus and P. zeae in soybean and corn, respectively, is evident. Additionally, P. thornei and abamectin in the form of seed treatment, show potential in mitigating yield losses caused by P. zeae in maize. This highlights the importance of P. thornei as an additional tool for the management of root lesion nematodes in soybean and maize, and should encourage subsequent work.